Rekonstruksi Diagnostic Test Four Tier Berbasis HOTS (High Order Thingking Skill) Pada Materi Fiqih Kelas X di MA Negeri 3 Jombang - Mahmudah, Fatati Nuriyana; Putra, Ino Angga; Wafa, Muhammad Aliyul; Franoto, Andi (Universitas KH. A. Wahab Hasbullah, 2023)
This research was conducted to develop an assessment instrument diagnostic test four tier. Diagnostic test four tier is one of the instruments used to diagnose student’s level of conception oon a concept. The purpose of this study was to design a four-tier diagnostic test assessment instrument based on high order thinking skills (HOTS) and also to determine the feasibility of understanding student’s concept that were valid and reliable. This research is a development research that uses a 4-D model, namely define, design, develop, and disseminate. The data analysis technique uses validation, validit, reliability and difficulty level and using SPSS 21 calculations. The results of the overall validation obtained that the average score of the four-tier diagnostic test instrument was 3.04 and valid or suitable for use. The results of the instrument validity test obtained 17 valid questions and the results of the instrument reliability test obtained a value of 0.901 in the very high category. Therefore, the four-tier diagnostic test assessment instrument based on high order thinking skills (HOTS) on fiqh material for class X MA Negeri 3 Jombang deserves to be tested in the learning process.